Teorização sobre o acesso ao cuidado em saúde bucal por mulheres trans e travestis profissionais do sexo: um estudo qualitativo - Félix, Thallys Rodrigues (2024)
Introduction: Prejudice and social discrimination suffered by trans and transvestite people have an impact on their quality of life and negatively affects access to health services. This situation can be worsened due to sex work, which is also socially stigmatized. Objective: To theorize about the meanings constituted by trans women and transvestite sex workers regarding access to oral health care. Methodology: Qualitative research was carried out, anchored in Symbolic Interactionism, with trans women and transvestite sex workers. The sample was intentional and delimited by theoretical saturation. Data were collected through semi-structured interviews and analyzed using Grounded Theory. The final theorization was carried out with input from the theoretical framework of the Patient-Centered Care Access Model. Results: Nine interviews were carried out, whose analysis and theorization produced eight categories, namely: Approachability, Acceptability, Availability and Accommodation, Appropriateness, Ability to perceive, Ability to seek, Ability to reach and Ability to pay. Access limitations are still impacted by prejudice arising from health professionals, but also by the need for long waits for care, which contrasts with the need for permanent availability for sex work. From the perspective of the women interviewed, prostitution increases the risk of developing diseases and acts as a motivator for seeking health services. Conclusion: Waiting time was indicated as a form of prejudice and limitation of access, as it clashes with the availability of times needed for work, requiring adjustments in interpersonal relationships (professional patient) and scheduling methods, which must consider social vulnerability as a prioritization criterion.